Kemas Ulang Informasi Permainan Tradisional Minangkabau di Kabupaten Pesisir Selatan - Yenti, Nadia Putri; Nurizzati, Nurizzati (Program Studi Informasi, Perpustakaan, dan Kearsipan , Jurusan Bahasa dan Sastra Indonesia, 2018)
Abstract Â The writing of this paper is motivated by the absence of a special source of information about mnangkabau traditional game in pesisir selatan district. The purpose of this research is to introduce traditional games to the upcoming young generation and to design traditional minangkabau game information packs in pesisir selatan district. The method used in writing this paper is a descriptive method with data collection techniques through observation ann interview. The processof design stage of making the repacking box is: a) identification user needs, b) conducting inspection of information collection and selection of information resources, c) choose sources that countain useful information values, d) evaluate the validity of the information, e) review, analyze, extract information into the form of more effective and efficient information for the user, f) repacking the information into an interesting book form with the intention that every information user can be interested and eager to read for all ages, h) disseminate information by way of promotion starting from the library, social media, brochures and so on.Keywords: repackage information, traditional game.